MODALITAS POLITIK PEMENANGAN BUPATI PEREMPUAN PERTAMA DI KABUPATEN KARANGASEM (STUDI KASUS: KEMENANGAN GUSTI AYU MAS SUMATRI DALAM PILKADA KARANGASEM TAHUN 2015) (Jurnal Nawala Politika, 2023)
Women's rights in the dynamics of political power in Bali tend to be placed in a space that is not exponential. In the constellation of regional elections in Bali, the election of women as regional heads is only filled in 2 out of 9 regencies, where one of the women's election occurred in Karangasem Regency. In the 2015 Karangasem regional head election (Pilkada), I Gusti Ayu Mas Sumatri in the candidate pair "Mas-Dipa" was declared the elected Karangasem Regent for the period 2016 - 2021, with 104,560 (41.76%) votes. This research uses a qualitative research method with a descriptive and analytical approach. The literature sources in this research consist of primary and secondary data sources, where primary literature is obtained from journals and research reports, while secondary literature is obtained from magazines, newspapers, and news articles in online media. Based on the data and findings, it is concluded in this study that the modalities are: Economic Capital, Social Capital; and Political Capital owned in the background of I Gusti Ayu Mas Sumatri then supported her to win the triangular constellation of battles in the 2015 Karangasem Regional Election. The modalities owned were able to be utilized well with the application of political strategies during her campaign period, such as: Obtaining Networks/Support; Formulating Campaign Strategies; Escorting Vote Acquisition; Formation of Campaign Teams; and Organizing Campaigns. Keywords: Electoral Modalities, I Gusti Ayu Mas Sumatri, Victory in the 2015 Karangasem Regional Election.